TINDAK TUTUR EKSPRESIF MEMINTA MAAF TERPIDANA KORUPSI DI INDONESIA - Nur Lailiyah (Prasasti: Journal of Linguistics, 2021)
This research is in the form of a qualitative descriptive which aims to explain the strategies of expressive speech acts to apologize by convicts of corruption that occurred in Indonesia in 2020. The data is in the form of speeches collected from online media and YouTube using documentation techniques through note-taking. Qualitative research methods using a pragmatic approach. The analysis focuses on how the lingual forms of apologetic speech acts and how the speech act strategies are. used by corruption convicts as well as the speech act function of apologizing. The results of this study were three expressive speech act strategies of apologizing expressed by the convicts of corruption, namely strategies by expressing apologies directly using the word sorry, apology strategies by providing additional explanations, speech act strategies to express apologies express accountability. Meanwhile, there are functions of speech acts in apologizing, namely: rebuilding (reconstructing) trust, rehabilitating oneself (individuals), healing from shame, resolving conflicts, and restoring social harmony.